Cysteines and Disulfide Bonds as Structure-Forming Units: Insights From Different Domains of Life and the Potential for Characterization by NMR - Wiedemann, Christoph; Kumar, Amit; Lang, Andras; Ohlenschläger, Oliver (Frontiers in Chemistry, 2020)
Disulfide bridges establish a fundamental element in the molecular architecture of proteins and peptides which are involved e.g. in basic biological processes or acting as toxins. NMR spectroscopy is one method to characterize the structure of bioactive compounds including cystine-containing molecules. Although the disulfide bridge itself is invisible in NMR, constraints obtained via the neighboring NMR-active nuclei allow to define the underlying conformation and thereby to resolve their functional background. In this mini-review we present an overview of recent NMR applications for the characterization of disulfide-bond containing biomolecules including advantages and limitations of the different approaches.